Percutaneous Transluminal Angioplasty and Drug-Eluting Stents for Infrapopliteal Lesions in Critical Limb Ischemia (PADI) Trial. (February 2016) - Spreen, Marlon I.; Martens, Jasper M.; Hansen, Bettina E.; Knippenberg, Bob; Verhey, Elke; van Dijk, Lukas C.; de Vries, Jean-Paul P.M.; Vos, Jan-Albert; de Borst, Gert Jan; Vonken, Evert-Jan P.A.; Wever, Jan J.; Statius van Eps, Randolph G.; et al.
Abstract : Background—: Endovascular infrapopliteal treatment of patients with critical limb ischemia using percutaneous transluminal angioplasty (PTA) and bail-out bare metal stenting (BMS) is hampered by restenosis. In interventional cardiology, drug-eluting stents (DES) have shown better patency rates and are standard practice nowadays. An investigator-initiated, multicenter, randomized trial was conducted to assess whether DES also improve patency and clinical outcome of infrapopliteal lesions. Methods and Results—: Adults with critical limb ischemia (Rutherford category ≥4) and infrapopliteal lesions were randomized to receive PTA±BMS or DES with paclitaxel. Primary end point was 6-month primary binary patency of treated lesions, defined as ⩽50% stenosis on computed tomographic angiography. Stenosis >50%, retreatment, major amputation, and critical limb ischemia–related death were regarded as treatment failure. Severity of failure was assessed with an ordinal score, ranging from vessel stenosis through occlusion to the clinical failures. Seventy-four limbs (73 patients) were treated with DES and 66 limbs (64 patients) received PTA±BMS. Six-month patency rates were 48.0% for DES and 35.1% for PTA±BMS ( P =0.096) in the modified-intention-to-treat and 51.9% and 35.1% ( P =0.037) in the per-protocol analysis. The ordinal score showed significantly worse treatment failure for PTA±BMS versus DES ( P =0.041). The observed major amputation rate remained lower in the DES group until 2 years post-treatment, with a trend toward significance ( P =0.066). Less minor amputations occurred after DES until 6 months post-treatment ( P =0.03). Conclusions—: In patients with critical limb ischemia caused by infrapopliteal lesions, DES provide better 6-month patency rates and less amputations after 6 and 12 months compared with PTA±BMS. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00471289. Abstract : Supplemental Digital Content is available in the text.